Motor habit teaching methods to improve the stress level of wrestlers in competition - Tobar Piedra, Freddy Israel; Aguilar Morocho, Elva Katherine (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
This study will be useful for all sports initiation level coaches, since we will present in depth the learning levels of a wrestler’s motor habit. We have identified the different stages and how to handle the real stress of a competition. Therefore, the objective of this research was to establish a methodological guide for teaching motor habit, through the different processes and principles of sports training, to improve stress levels in competition of wrestlers. This research is experimental and quantitative in nature. We worked with a study population of 16 athletes from the school category Olympic wrestling discipline. The following tests were applied to the wrestlers: basic motor skills test, specific motor habit test, and divided anxiety test (somatic, cognitive and self-confidence). It was determined that anxiety can influence the sporting performance of wrestlers, but this anxiety is in turn related to the level of technical mastery. Therefore, the sports initiation stage of children must be correct and an appropriate methodology must be applied to improve their technical mastery.